2005
DOI: 10.1262/jrd.51.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Grafting on Follicular Growth in Porcine Ovarian Cortical Grafts Xenoplanted to Severe Combined Immunodeficient (SCID) Mice

Abstract: Abstract. To establish a tool for the study of follicular growth and development, we xenotransplanted small pieces (approximately 1 mm 3 ) of porcine ovarian cortical tissues containing only primordial follicles and small preantral follicles under the capsules of kidneys of severe combined immunodeficient (SCID) mice (8-10 weeks old). The changes in cell proliferation and cell death/ apoptosis, and vascularization in xenotransplanted follicles during follicular growth and development were analyzed histochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In the 8 weeks group, many tertiary follicles with large antral cavities were observed on the surface of the grafted tissues. As noted in our previous report [20], large tertiary follicles and a progressed and expanded neovascularization were seen on the surface of antral follicles in the 2 weeks group under the dissecting microscope. In the recovered ovarian tissues, some of the growing tertiary follicles with large and clear antral cavities had oocytes, which remained at the GV stage (Table 2).…”
Section: Follicular Growth In Porcine Ovarian Tissues Xenografted In supporting
confidence: 84%
See 2 more Smart Citations
“…In the 8 weeks group, many tertiary follicles with large antral cavities were observed on the surface of the grafted tissues. As noted in our previous report [20], large tertiary follicles and a progressed and expanded neovascularization were seen on the surface of antral follicles in the 2 weeks group under the dissecting microscope. In the recovered ovarian tissues, some of the growing tertiary follicles with large and clear antral cavities had oocytes, which remained at the GV stage (Table 2).…”
Section: Follicular Growth In Porcine Ovarian Tissues Xenografted In supporting
confidence: 84%
“…The tissue pieces contained many preantral follicles, which were less than 0.3 mm in diameter. Then, as previously reported [20], they were xenotransplanted under the kidney capsules of adult female severe combined immunodeficient (SCID) mice, which lack T or B lymphocytes but not natural killer cells are considered to be an in vivo model of the human immune system, and are used as recipients for xenotransplantation, to establish an experimental model that provides fundamental information on follicular growth and development in grafted tissues and that aids in understanding the mechanisms of individual follicular growth and/or atresia. Based on our previous findings [20], oocytes that were more than 0.5 mm in diameter collected 2 and 8 weeks after xenotransplantation from growing tertiary follicles, in the xenotransplanted tissues of porcine ovaries were cultured for in vitro maturation (IVM) to assess the quality of each oocyte.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Snow et al (2002) demonstrated that oocytes that grow within mouse ovarian tissue xenografted to nude rats acquire the ability to generate pups. Ovarian tissues have been prepared from species phylogenetically distant from mice, including humans (Oktay et al 1998, Weissman et al 1999, Kim et al 2002, Gook et al 2003, dogs (Metcalfe et al 2001), monkeys (Candy et al 1995), sheep (Gosden et al 1994), cows (Senbon et al 2003), pigs (Kaneko et al 2003, Kagawa et al 2005, tammar wallaby (Mattiske et al 2002) and common wombats (Cleary et al 2003(Cleary et al , 2004, and xenografted to immunodeficient mice. To our knowledge, only one study (Kaneko et al 2003), in which neonatal pig ovarian tissues were xenografted, has proven that primordial oocytes can develop in the host mice and acquire fertilizing ability in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse oocytes that grow within ovarian tissue xenografted to nude rats acquire the ability to generate pups [3]. Moreover, ovarian tissues have been prepared from species phylogenetically distant from mice, including humans [4][5][6][7], dogs [8], monkeys [9], sheep [10], cows [11], pigs [12,13], tammar wallabies [14], and common wombats [15,16], and xenografted into immunodeficient mice. To date, there has only been one report [12] stating that primordial oocytes can develop in host mice and acquire fertilizing ability in vitro.…”
mentioning
confidence: 99%